Comparison of Antibody Status Following COVID-19 Vaccination between SARS-Cov-2 Infected and Non-infected Healthcare Professionals of Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh - Romana, Rimpi; Mollah, Forhadul Hoque; Brishti, Tanha Waheed; Mozaffor, Miliva; Nurunnabi, Abu Sadat Mohammad; Zarin, Ismet (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Antibody developed through COVID-19 vaccination plays a vital role in combating further infection and suppressing pathogenesis of SARS-CoV-2. This study aims to observe the difference in antibody status between COVID-19 infected and non-infected healthcare professionals following two doses of COVID-19 vaccine.METHODS This cross-sectional, analytical study was conducted in the Department of Biochemistry and Molecular Biology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between March 2021 and February 2022. A total of 70 adult participants (healthcare professionals) were included in this study from different departments of BSMMU Hospital. Study participants were categorized into two groups; each group had 35 participants. Group A includes healthcare professionals who were infected by SARS CoV-2 and later vaccinated by two doses of AstraZeneca COVID-19 vaccine, while Group B consists of those who were not infected by SARS CoV-2 but took two doses of AstraZeneca COVID-19 vaccine. We collected participants’ demographic profile and detailed history including co-morbidities and related test results in the data collection sheet. Serum IgG was assessed by chemiluminescent microparticle immunoassay method.RESULTS Serum IgG levels were found in group A as a median 2183.2 AU/ml with an IQR (inter quartile range) of 3852.0 AU/ml, while in group B, median was 624.7 AU/ml and IQR was 621.1 AU/ml (p